The Investors’ Perspective on Investment Attractiveness of Oil and Gas Exploration Industry in Indonesia - Riswan, Khaidir; Fani Cahyandito, Martha; Herwany, Aldrin; Anwar, Mokhamad (International Journal of Engineering and Technology, 2018)
As from the year 2011 to date, the oil and gas exploration (O&G) industry in Indonesia is not attractive anymore to the investors. It is clearly shown by all indicators of the O&G exploration performance in Indonesia which decline sharply causing the RRR (Reserves Replacement Ratio) is currently about 0.5. As the result the national O&G reserves and production decline as well. Starting the year 2004 Indonesia has become an oil nett impoter; the consumption is much bigger than the national production. This is threatening the availability of O&G energy source so that it can cause state instability. This study aims to conduct the assessment of the investors’ perspective on the investment attractivenesss of O&G exploration industry in Indonesia, taking into account two main variables, i.e: the Government Regulation and Global Environment Variables using Analytical Hierarchy Process (AHP) method. The units of analysis are the O&G investors which means the shareholders. Meanwhile, observation units are the top management and the managers of O&G companies in Indonesia. Result of the study shows that Government Regulation Variable is the worse variable to accommodate the investors’ expectation causing the low attractiveness of the O&G exploration industry in Indonesia. Surprisingly the influence of Global Environment variables, such as world crude oil price, is not significant compared to the Government Regulation. To increase the attractiveness of O&G exploration industry, Government of Indonesia should reform the existing regulation and increase government support for this industry to match the global environment which keeps changing.